Dynamics of ICT, Natural Resource, Green Innovation, and Environmental Sustainability in Developing-8 organization of Economic Cooperation Countries: A Cross-Sectional ARDL Approach - Atiq-ur-Rehman, Muhammad; Ramzan, Adnan; Hisham ul Hassan, Khwaja; Popescu, Virgil; Birau, Ramona; Nioata, Roxana-Mihaela; Margaritescu, Stefan (International Journal of Energy Economics and Policy, 2025)
The member states of developing-8 orD-8 organization for economic cooperation have been facing various environmental hitches posing different challenges. The interlinkages between information and communication technologies (ICT), natural resources, green finance, green innovation and environmental footprint are turning to be pivotal in this regard. This study examines the interrelationships among, natural resource rents (NRR), green technology innovation (GI), economic growth (EG), green finance (GF), and ecological footprints (EFP) in the D-8 member countries using data for the period 1995-2024. After checking data for the cross-sectional dependence (CSD), a cross-sectional augmented autoregressive distributive lag (CS-ARDL) approach is employed for the estimation. The empirical results show that natural resources increase ecological footprint. Green finance, information and communication technologies, green innovations, and technological advancements all contribute to reducing ecological footprints. The Dumitrescu and Hurlin (2012) causality testing show a one-way causal relationship between economic growth, green finance, ecological footprints, and information and communication technologies. This study incorporates new knowledge from the D-8 nations in the existing body of knowledge related to causes of environmental pollution. In addition, this study provides a benchmark by which policymakers and government institutions can evaluate their investments in the ICT, green finance, and environment-friendly technology to mitigate environmental emissions.